2006
DOI: 10.1016/j.cub.2006.08.053
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Food Anticipation in Per2 Mutant Mice

Abstract: Predicting time of food availability is key for survival in most animals. Under restricted feeding conditions, this prediction is manifested in anticipatory bouts of locomotor activity and body temperature. This process seems to be driven by a food-entrainable oscillator independent of the main, light-entrainable clock located in the suprachiasmatic nucleus (SCN) of the hypothalamus . Although the SCN clockwork involves self-sustaining transcriptional and translational feedback loops based on rhythmic expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
192
2
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(212 citation statements)
references
References 36 publications
16
192
2
2
Order By: Relevance
“…Our study thus provides evidence that plant nutrition, like in animals, is tightly linked to circadian functions as previously hypothesized (19). Recently, it was shown that the central clock gene Per2 is necessary for food anticipation in mice (33). Our data indicate that the central clock gene CCA1 plays a role in circadian regulation of Nassimilation in plants.…”
Section: Discussionsupporting
confidence: 82%
“…Our study thus provides evidence that plant nutrition, like in animals, is tightly linked to circadian functions as previously hypothesized (19). Recently, it was shown that the central clock gene Per2 is necessary for food anticipation in mice (33). Our data indicate that the central clock gene CCA1 plays a role in circadian regulation of Nassimilation in plants.…”
Section: Discussionsupporting
confidence: 82%
“…Hence, the circadian clock might also be important to predict food availability in mammals. In line with this hypothesis is the finding that mice with a mutation in the Per2 gene do not have food anticipatory activity (FAA) and temperature increase [75] indicating that PER2 is involved in food anticipation either in its function as a clock gene or via a clock-independent mechanism. Although other clock components such as NPAS2 or Mop3/BMAL1 show reduced food anticipation [19] recent experiments suggest that daily rhythms of FAA do not require the circadian clock [76].…”
Section: The Impact Of Clock Genes On Physiologymentioning
confidence: 89%
“…To study the rhythmic expression of clock genes in the cerebellum, mice under a light-dark cycle (LD) were used under two different feeding conditions. A group had free access to food (food ad libitum, AL), while another group (hypocaloric feeding: HF) was submitted to a temporal calorie restriction paradigm, in which animals received the 66% of daily food intake at midday [Zeitgeber time (ZT)6] for at least 3 weeks as described previously (Mendoza et al, 2005a;Feillet et al, 2006). On the last day of food restriction, mice were killed with isoflurane overdose and decapitated in 8 groups of 4 mice, at 3 h intervals starting at ZT0.…”
Section: Protocols Of Timed Feeding and Brain Samplingmentioning
confidence: 99%